Adapted cognitive behavior therapy for obsessive–compulsive disorder with co-occurring autism spectrum disorder: A clinical effectiveness study. (January 2020) - Flygare, Oskar; Andersson, Erik; Ringberg, Helene; Hellstadius, Anna-Clara; Edbacken, Johan; Enander, Jesper; Dahl, Matti; Aspvall, Kristina; Windh, Indra; Russell, Ailsa; Mataix-Cols, David; Rück, Christian
Obsessive–compulsive disorder and autism spectrum disorder commonly co-occur. Adapted cognitive behavior therapy for obsessive–compulsive disorder in adults with autism spectrum disorder has not previously been evaluated outside the United Kingdom. In this study, 19 adults with obsessive–compulsive disorder and autism spectrum disorder were treated using an adapted cognitive behavior therapy protocol that consisted of 20 sessions focused on exposure with response prevention. The primary outcome was the clinician-rated Yale–Brown Obsessive–Compulsive Scale. Participants were assessed up to 3 months after treatment. There were significant reductions on the Yale–Brown Obsessive–Compulsive Scale at post-treatment (d = 1.5), and improvements were sustained at follow-up (d = 1.2). Self-rated obsessive–compulsive disorder and depressive symptoms showed statistically significant reductions. Improvements in general functioning and quality of life were statistically non-significant. Three participants (16%) were responders at post-treatment and four (21%) were in remission from obsessive–compulsive disorder. At follow-up, three participants (16%) were responders and one (5%) was in full remission. Adapted cognitive behavior therapy for obsessive–compulsive disorder in adults with co-occurring autism spectrum disorder is associated with reductions in obsessive–compulsive symptoms and depressive symptoms. However, outcomes are modest; few patients were completely symptom free, and treatment engagement was low with few completed exposures and low adherence to homework assignments. We identify and discuss the need for further treatment refinement for this vulnerable group.